The international law of the sea India and the UN convention of 1982 - Sharma, O. P. (New Delhi ; Oxford : Oxford University Press, 2009)
The law of the sea has undergone more change in the last 50 years than it has in the previous 400. All naval operations are meant to be carried out within the framework ofinternational law, which now centres around the UN Convention on the Law of the Sea, 1982. An understanding of today's law of the sea is critical for domestic as well as international maritime trade and inevitably of course, for national security. This book provides clarity on what the legitimate use of ocean space is and what is not, examining the new jurisdictional boundaries or functional divisions of the oceans into several maritime zones along with their military implications.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law of the sea; Law of the sea -- India